New Mediterranean Biodiversity Records (July 2015) - K. TSIAMIS; Ö. AYDOGAN; N. BAILLY; P. BALISTRERI; M. BARICHE; S. CARDEN-NOAD; M. CORSINI-FOKA; F. CROCETTA; B. DAVIDOV; C. DIMITRIADIS; B. DRAGIČEVIĆ; M. DRAKULIĆ; et al. (Mediterranean Marine Science, 2015)
The Collective Article ‘New Mediterranean Biodiversity Records’ of the Mediterranean Marine Science journal offers the means to publish biodiversity records in the Mediterranean Sea. The current article is divided in two parts, for records of native and alien species respectively. The new records of native species include: the neon flying squid Ommastrephes bartramii in Capri Island, Thyrrenian Sea; the bigeye thresher shark Alopias superciliosus in the Adriatic Sea; a juvenile basking shark Cetorhinus maximus caught off Piran (northern Adriatic); the deep-sea Messina rockfish Scorpaenodes arenai in the National Marine Park of Zakynthos (East Ionian Sea, Greece); and the oceanic puffer Lagocephalus lagocephalus in the Adriatic Sea.The new records of alien species include: the red algae Antithamnionella elegans and Palisada maris-rubri, found for the first time in Israel and Greece respectively; the green alga Codium parvulum reported from Turkey (Aegean Sea); the first record of the alien sea urchin Diadema setosum in Greece; the nudibranch Goniobranchus annulatus reported from South-Eastern Aegean Sea (Greece); the opisthobranch Melibe viridis found in Lebanon; the new records of the blue spotted cornetfish Fistularia commersonii in the Alicante coast (Eastern Spain); the alien fish Siganus luridus and Siganus rivulatus in Lipsi Island, Dodecanese (Greece); the first record of Stephanolepis diaspros from the Egadi Islands Marine Protected Area (western Sicily); a northward expansion of the alien pufferfish Torquigener flavimaculosus along the southeastern Aegean coasts of Turkey; and data on the occurrence of the Lessepsian immigrants Alepes djedaba, Lagocephalus sceleratus and Fistularia commersonii in Zakynthos Island (SE Ionian Sea, Greece).